New Faces of old Friends: Emerging new Roles of RNA-Binding Proteins in the DNA Double-Strand Break Response - Klaric, Julie A.; Wüst, Stas; Panier, Stephanie (Frontiers in Molecular Biosciences, 2021)
DNA double-strand breaks (DSBs) are highly cytotoxic DNA lesions. To protect genomic stability and ensure cell homeostasis, cells mount a complex signaling-based response that not only coordinates the repair of the broken DNA strand but also activates cell cycle checkpoints and, if necessary, induces cell death. The last decade has seen a flurry of studies that have identified RNA-binding proteins (RBPs) as novel regulators of the DSB response. While many of these RBPs have well-characterized roles in gene expression, it is becoming increasingly clear that they also have non-canonical functions in the DSB response that go well beyond transcription, splicing and mRNA processing. Here, we review the current understanding of how RBPs are integrated into the cellular response to DSBs and describe how these proteins directly participate in signal transduction, amplification and repair at damaged chromatin. In addition, we discuss the implications of an RBP-mediated DSB response for genome instability- and age-associated diseases such as cancer and neurodegeneration.